5(x-4)=3(2-x)

Simple and best practice solution for 5(x-4)=3(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)=3(2-x) equation:



5(x-4)=3(2-x)
We move all terms to the left:
5(x-4)-(3(2-x))=0
We add all the numbers together, and all the variables
5(x-4)-(3(-1x+2))=0
We multiply parentheses
5x-(3(-1x+2))-20=0
We calculate terms in parentheses: -(3(-1x+2)), so:
3(-1x+2)
We multiply parentheses
-3x+6
Back to the equation:
-(-3x+6)
We get rid of parentheses
5x+3x-6-20=0
We add all the numbers together, and all the variables
8x-26=0
We move all terms containing x to the left, all other terms to the right
8x=26
x=26/8
x=3+1/4

See similar equations:

| X²+11x=-30 | | X²+42=13x | | 1/3x–1/5=0,8 | | 25=-0.5x+104.75 | | T=3a-15 | | 4.5+y/8=-8.3 | | t^2-13.32t-0.8=0 | | 32=n=50 | | 24=18+2y | | 4(x+2)-(x-10)=x+4 | | 7x-2=7x+14 | | 5000*0.04=x | | (85)+(5x-1)+(8x+5)=180 | | 2+5x-x^2=-2 | | 5x+2=2×+12 | | 3x+9x-7+2x+5=180 | | (b-4)/(6)=(b)/(2) | | 3x+9x+7+2x+5=180 | | 4x-9=6=x | | 14x+28/49x-49=0 | | 6x-5=13-33x | | 25x+4=159 | | 8+3p-5=15 | | 3(x+2x)+18=27 | | 100-3x=19 | | 3(x+2x)+18=37 | | 3n+17=60 | | 432+0,2x=144x | | 6x+60=4-4x | | x+52=102 | | 102=52+x | | 7/18m=3/5 |

Equations solver categories